APLICACIÓN DE LA TEORÍA BASADA EN LOS RECURSOS EN EL AGROPARQUE AHUALULCO, S.A DE C.V. - José Vargas Hernandez; Pablo A. Magaña Sánchez; Daniel Hernandez Medina (Boletín Geográfico)
The vision based on resources and capabilities is of vital importance for understanding the performance with competitive companies. In this paper we take into account this vision to study the case of the company AgroPark Ahualulco SA de C.V. and as the implementation of resources and capabilities have led to its growth in the past two years. The aim of this paper is to analyze the implementation of the vision based on resources and capabilities to propose solutions to problems that may arise in the company AgroPark Ahualulco SA de CV Based on quantitative data collected and having applied the theory based on resources and capabilities relevant information was obtained for decisions of the owners of AgroPark Ahualulco SA de C.V. The knowledge generated by this research gives them more accurate and credible tools with which to further understand your business. Dominating widely knowledge about the resources and capabilities they possess really can make better decisions on the efficient use of these. It concludes that despite being a new company AgroPark Ahualulco SA de CV, operates efficiently, the business in the current operating point generates positive benefits seen from the economic approach. This conclusion is based on the efficient use of resources and the company also makes good use of its installed capacity. Your breakeven point indicates that Ahualulco AgroPark products have a high margin of profit contribution; this works as a reserve to the normal risks with companies in the agricultural field, comparatively to the company to cover its fixed costs are relatively few boxes that need to sell. Finally the possibility of a halt in production caused by the company supplies its products to only one customer is identified. Derived from analysis of consumer surplus we can conclude that there is a high potential demand and producer surplus gives support to say that such demand if it can be covered, the above can be achieved with appropriate reinvestment of profits, which have as business growth results.